2015
DOI: 10.1177/1545968315619698
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Exercise Is Ineffective at Reversing Aberrant Nociceptive Afferent Plasticity or Neuropathic Pain After Spinal Cord Injury in Rats

Abstract: Neuropathic pain is a debilitating consequence of spinal cord injury (SCI) that correlates with sensory fiber sprouting. Recent data indicates that exercise initiated early after SCI prevents the development of allodynia and modulated nociceptive afferent plasticity. This study determined if delaying exercise intervention until pain is detected would similarly ameliorate established SCI-induced pain. Adult, female Sprague-Dawley rats with a C5 unilateral contusion were separated into SCI allodynic and SCI non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 73 publications
(125 reference statements)
2
37
0
Order By: Relevance
“…exercise initiated after injury) in human chronic pain populations are mixed, mainly due to differences in type of pain, type of exercise and exercise intensity [40; 55; 67; 72; 95]. In contrast, rodent studies employing therapeutic exercise uniformly show robust analgesic effects in a variety of persistent pain models and using a variety of exercise intensities [4; 9; 11; 1824; 34; 35; 41; 54; 63; 69; 81; 82; 93; 102; 103; 112; 132]. Importantly, none of these studies assessed stress-related outcomes such as plasma corticosterone despite employing forced running paradigms that can be highly stressful [28; 36; 48; 62; 74; 80; 88; 89; 92].…”
Section: Introductionmentioning
confidence: 99%
“…exercise initiated after injury) in human chronic pain populations are mixed, mainly due to differences in type of pain, type of exercise and exercise intensity [40; 55; 67; 72; 95]. In contrast, rodent studies employing therapeutic exercise uniformly show robust analgesic effects in a variety of persistent pain models and using a variety of exercise intensities [4; 9; 11; 1824; 34; 35; 41; 54; 63; 69; 81; 82; 93; 102; 103; 112; 132]. Importantly, none of these studies assessed stress-related outcomes such as plasma corticosterone despite employing forced running paradigms that can be highly stressful [28; 36; 48; 62; 74; 80; 88; 89; 92].…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, the vast majority of studies (36 or 90%) reported that at least some form of therapeutic exercise was effective in reducing or reversing mechanical hypersensitivity. While three of the four studies showing no beneficial effect of therapeutic exercise on mechanical hypersensitivity initiated exercise 8 or more days after injury [ 92 , 98 , 118 ], other studies using similar delays in initiation of exercise were effective [ 87 , 91 •, 114 ••, 116 , 119 , 120 ]. Similarly, while two of the four studies showing no beneficial effect of therapeutic exercise on mechanical hypersensitivity used voluntary exercise paradigms [ 98 , 101 ], other studies using voluntary exercise were effective [ 87 , 97 , 99 ••, 100 ••].…”
Section: Is Exercise Beneficial In Rodent Models Of Chronic Pain?mentioning
confidence: 99%
“…atrophic changes versus increases in volume) and may provide substrates for the underlying neural mechanisms in the development of NP. 16,17 Anticonvulsants remain the most studied and supported pharmacotherapy for NP post-SCI. Antidepressants likely showed reduction in pain only among those with comorbid depression.…”
Section: Discussionmentioning
confidence: 99%